Fecal microbiota transplantation in irritable bowel syndrome: A meta-analysis of randomized controlled trials - Samuthpongtorn, Chatpol; Kantagowit, Piyawat; Pittayanon, Rapat; Patcharatrakul, Tanisa; Gonlachanvit, Sutep (Frontiers in Medicine, 2022)
Introduction Fecal microbiota transplantation (FMT) has been proposed as a potential treatment for irritable bowel syndrome (IBS); however, the consensus regarding its efficacy and safety is limited. Materials and Methods We performed a systematic search of the literature using PubMed, EMBASE, Ovid MEDLINE, and Cochrane. Meta-analyses were conducted in relative risk (RR) or standard mean difference (SMD) using 95% confidence intervals (CI). Cochrane risk-of-bias 2 tool (RoB2) was employed to evaluate the study quality. Result Of 2,589 potential records, 7 studies with 9 cohorts involving 505 participants were included. Meta-analyses showed no significant difference in the short-term (12 weeks) and long-term (12 months) global improvement of IBS symptoms of FMT vs. placebo (RR 0.63, 95% CI 0.39–1.00 and RR 0.88, 95% CI 0.53–1.45, respectively). There were statistically significant differences of short-term IBS-SSS improvement (SMD –0.58, 95% CI –1.09 to –0.88) and short-term IBS-QoL improvement (SMD 0.67, 95% CI 0.43–0.91). Eight from 9 studies (88.9%) had a low risk of bias. The subgroup analysis revealed the short-term global symptoms improvement in studies with low-risk of bias (RR 0.53, 95% CI 0.35–0.81), studies with well-defined donors (RR 0.31, 95% CI 0.14–0.72), and studies with FMT using colonoscopy (RR 0.66, 95% CI 0.47–0.92). Major FMT adverse events are transient and rapidly self-limiting. Conclusion FMT significantly improved IBS-SSS and IBS-QoL in the short-term period in IBS patients. However, global symptom improvement showed no significance. Well-defined donors and appropriate fecal administration routes appear to be important factors for the successful outcomes of FMT in IBS. Systematic review registration [www.crd.york.ac.uk/prospero], identifier [CRD42021246101].